Analysis of manufacturer’s recommendations for the use of vibratory plate compactors - Afanasev M.A.; Tyuremnov I.S. (Naučno-Tehničeskij Vestnik Brânskogo Gosudarstvennogo Universiteta)
Self-propelled vibratory plate compactors are surface compaction machines with a flat operating device, which is introduced into a state of oscillatory movements and causes the movement of the machine itself along the soil surface. Industrially produced plate compactors differ significantly in technical specifications, which causes differences in the effectiveness of their use on different types of soil and under various conditions. This fact sufficiently complicates both the design of new models of vibratory plate compactors and the selection of suitable models for soil compaction under various conditions. A significant part of manufacturers provides limited recommendations of the technological capabilities of various models of vibratory plate compactors which increases the risk of insufficient soil compaction and a decrease in the service life of structures built on it. The purpose of the study was to collect data on industrially produced models of vibratory plate compactors, as well as to analyze manufacturers recommendations for the use of vibratory plate compactors in various conditions. The collected data allows us to evaluate the gathered experience in the development and improvement of model lines of vibratory plate compactors and can be used when designing new models of vibratory plate compactors.